A descriptive survey on the factors that influence the sustainability of selected interior design projects facilitated under ID 179 special projects course - Mananghaya, Karla Therese M.
The study aimed to determine the factors that influence the sustainability of the interior design of selected projects by UP BSID students facilitated under their ID179 Special Projects Course from year 2004-2014. A multiple-case study approach was applied wherein eleven (11) projects pertaining to cases were evaluated through triangulation method which involved: observation of the current physical conditions of the projects; photo-documentation of the changes that have happened to the interiors; and interview with the project beneficiaries. Twenty (20) beneficiaries were interviewed; one (1) to two (2) interview respondents from each project. In this study, sustainability was defined as maintainability; longevity; ability to withstand wear and tear, to remain functional and suitable to the needs and activities of the beneficiaries, within the span of five (5) years. The study revealed common problems in the interiors of the selected projects, namely: damaged built-in furniture, damaged floor finish, and not properly maintained spaces. Common changes that have happened in the project were also found, such as: repositioning of furniture and accessories, repainting of walls, and replacement or removal of accessories. Three (3) projects were observed to have different functions from their initial purpose. Findings indicate that from the eleven (11) completed projects studied, four (4) projects were identified as sustainable; five (5) were not sustainable; and two (2) projects cannot be determined yet because they do not fall under the five-year criteria. The following were enumerated as factors that influence the sustainability of the interior design of the selected ID179 projects: 1) dwellers or users of the renovated facility; their efforts in maintaining the condition of the project, their preferences, and their activities, 2) environmental factors, such as: typhoons and floods, 3) budget or funding of both the ID179 project and the selected beneficiary, 4) time; age of the project and length of construction, and 5) materials used for furniture and furnishings.